PENGARUH PEMBERIAN RUSIP TERHADAP GARAM EMPEDU FECES DAN KOLESTEROL TOTAL TIKUS HIPERKOLESTEROLEMIA - Muhammad Duddy Satrianugraha (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2015)
This study aims to confirm the effect of Rusip administration on levels of fecal bile salts and serum total cholesterol in hypercholesterolemic mice. This study uses the Randomized Pre and Post Controlled Group Design. Twenty-eight male Sprague Dawley white mice with normal weight were given a high-fat high cholesterol diet, then divided into 2 groups, namely control and treatment given Rusip 5.10 mg / gr bb / day. After 28 days of treatment, stool and blood samples were taken to determine the levels of fecal bile salts and serum total cholesterol using the enzymatic method. Statistically testing differences between groups at a 95% confidence level. The administration of ripple in hypercholesterolemic rats for 14 days significantly managed to increase the release of bile salts through the stool and reduce serum total cholesterol levels. Lactic acid bacteria can de-conjugate primary bile salts into secondary bile salts which are more difficult to reabsorb by the body through enterohepatic circulation by apical sodium codependent bile acid transporter (ASBT) or Ileal Na + / bile acid cotransporter (IBAT). Along with not being reabsorbed bile salt, fat and cholesterol in food that should be absorbed into the body along with bile salts as emulsifiers, come out with the stool. This whole mechanism causes a decrease in total cholesterol in the blood plasma. Rusip's administration significantly caused an increase in bile salts in the stool and decreased serum total cholesterol in hypercholesterolemic mice.